طاہر سُلطانی کی نعتیہ شاعری میں تذکرۂ دُرود و سلام: Narration of Durood-o-Salām in Tahir Sultani’ s Na̒tia Poetry (Al-Qamar, 2021)
Urdu Poetry has a distinct among its so many other forms. Among them Na'at has gained a unique, sacred and dominating place all over the other forms. The Poets consider it an honour for them to write Na'at-e-Nabi (S.A.W). While writing the Na'at they consciously try to write about the life and characteristics of the Holy Prophet Hazrat Muhammad (S.A.W). They also write about Darood-o-Salam which the Allah Almighty has made an obligation for the Muslims. Darood is the most important subject of the poet and most of his poetry is relevant to it. Tahir Sultani belongs to the district Karachi, is a poet of Na’at and Hamd. He has been writing Na’at-e-Rasool (S.A.W) for the last two decades. He has published Works based on the above-mentioned types of poetry with the Titals “Na̒t Roshni”, “Naat Meri Zindagi” and " Har Saans Pukaray Sall-e-Ala". Tahir Sultani has also gaind the fame as a critic. In this article the poet’s feelings about the Holy Prophet (S.A.W) and his style of mentioning the facts has been discussed with respect to the above-mentioned books.
Keywords: Tahir Sultani; Na̒t, characteristics